Isolation of winged bean (Psophocarpus tetragonolobus L.) allergen protein to create skin prick test reagent - Lusiana Lusiana, Fransiska Rungkat Zakaria, Endang Prangdimurti, Hendra Wijaya (Journal of Applied Pharmaceutical Science, 2023)
Any type of food that contains protein can cause allergies. The winged bean (Psophocarpus tetragonolobus L.) is a type of legume plant that contains high protein, and it is quite abundant in West Java, Indonesia. There are no specific studies discussing allergies to winged bean plants. This study aimed to isolate the protein of the winged bean (P. tetragonolobus L.) and characterize the allergenicity of the protein isolate using ELISA and immunoblotting and test the reactivity by the skin prick testing method. The fresh winged bean (FWB) protein profile had 13 protein bands (22–89 kDa). The boiled winged bean (BWB) contained 10 bands (22–73 kDa). The results of immunoblotting of 10 allergy-positive respondents whose serum was taken showed that the FWB protein can bind to specific IgE antibodies in respondent 1 in the protein band with a molecular weight (MW) of 24 kDa, respondent 5 with a MW of 219 kDa, respondent 7 with MWs of 29 and 23 kDa, and respondent 9 with a MW of 17 kDa. Meanwhile, the BWB protein can bind to specific IgE antibodies in respondents 7 and 8. In the BWB sample, the allergen protein was bound to specific IgE only in respondent 7 with MWs of 31 and 24 kDa and respondent 8 with MWs of 31 and 23 kDa.